DOES EMOTIONAL EATING MEDIATE THE EFFECT OF PHYSICAL ACTIVITY AND SLEEP DURATION ON FAT INTAKE IN PREGNANT WOMEN? - Aisyah Fariandini; Mohammad Fanani; Sri Mulyani (Media Gizi Indonesia, 2022)
Pregnant women need nutrients, one of which is fat. High fat intake might occur due to emotional eating. Emotional eating and excessive fat intake are assumed to be caused by low physical activity and insufficient sleep duration. This study purposed to investigate whether emotional eating mediates the effect of physical activity and sleep duration on fat intake in pregnancy. This study used an analytic survey method with a cross-sectional approach. The population of this study was pregnant women in the second and third trimesters who lived in Bondowoso Regency. Sampling was conducted with a cluster random sampling technique, and 105 subjects were obtained. The research instruments included a 24-hour food recall form, Emotional Eater Questionnaire (EEQ), Pregnancy Physical Activity Questionnaires (PPAQ), and four sleep duration questions from the Pittsburgh Sleep Quality Index (PSQI) form. Statistical test used path analysis. The direct influences in this study were shown by the variables of physical activity and sleep duration on emotional eating (p-values 0.027 and <0.001), and emotional eating on fat intake of pregnant women (p-value <0.001), respectively. Emotional eating can explain the effect of physical activity and sleep duration on fat intake with the indirect effect value greater than that with the direct effect. The conclusion of this study is that there is a role for emotional eating to mediate the indirect effect of physical activity and sleep duration on fat intake. Women who are pregnant should be able to do dietary habit, regulate sleep, and physical activity.